Comparing teachers’ grit in teaching four English skills in Islamic high schools - Zulfah Fakhruddin; Nur Afiah (Universitas Muhammadiyah Malang, 2026)
This study aims to describe and to compare teachers’ grit level in teaching four English skills (listening, speaking, reading, and writing skills) within Islamic high schools in Parepare, South Sulawesi, Indonesia. Using a quantitative survey design, data were collected from 24 English teachers through a questionnaire adapted from Duckworth and Quinn's Scale, which measured two dimensions of grit (perseverance of effort and consistency of interest) The data analyzed descriptively and inferentially using the Friedman test to determine differences among the four skills. Findings revealed that teachers generally demonstrated a high level of grit in teaching all English skills. However, significant differences were observed among the skills, with reading showing the highest level of grit, followed by writing, speaking, reading, and listening. Listening showed the most uniform grit distribution, while writing revealed the widest variability. These differences indicate that the instructional and emotional demands of each skills affect teachers' perseverance and consistency in teaching. The study concludes that grit plays a vital role in sustaining teachers' motivation and resilience across diverse teaching contexts. The Implication suggest the need for targeted professional development programs to enhance teachers' grit, particularly in teaching productive skills by fostering adaptive instructional strategies, emotional resilience, and pedagogical self-efficacy to ensure effective English language instruction and improved students' outcome.